2019
DOI: 10.1186/s12883-019-1554-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the cerebrospinal fluid ctDNA detection by next-generation sequencing in the diagnosis of meningeal Carcinomatosis

Abstract: BackgroundMeningeal carcinomatosis (MC) is the most severe form of brain metastasis and causes significant morbidity and mortality. Currently, the diagnosis of MC is routinely confirmed on the basis of clinical manifestation, positive cerebrospinal fluid (CSF) cytology, and/or neuroimaging features. However, negative rate of CSF cytology and neuroimaging findings often result in a failure to diagnose MC from the patients who actually have the disease. Here we evaluate the CSF circulating tumor DNA (ctDNA) in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…In addition, CSF liquid biopsy does not suffer from the inherent problems of tissue biopsy that commonly hamper subsequent molecular analysis, such as inadequacy and formalin fixation, and could depict intra-tumor heterogeneity more comprehensively, especially when compared to small biopsies [ 62 , 63 , 66 , 193 ]. Likewise, it exhibits higher sensitivity to detect leptomeningeal metastases than imaging or CSF cytology [ 62 , 95 98 ]. Evidence suggests that CSF liquid biopsy should be favored over its plasma counterpart when evaluating a CNS tumor, either primary or metastatic, as it shows a higher concentration of ctDNA and a higher mutation detection rate, and it depicts the CNS lesion molecular profile more accurately, especially when dealing with brain metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, CSF liquid biopsy does not suffer from the inherent problems of tissue biopsy that commonly hamper subsequent molecular analysis, such as inadequacy and formalin fixation, and could depict intra-tumor heterogeneity more comprehensively, especially when compared to small biopsies [ 62 , 63 , 66 , 193 ]. Likewise, it exhibits higher sensitivity to detect leptomeningeal metastases than imaging or CSF cytology [ 62 , 95 98 ]. Evidence suggests that CSF liquid biopsy should be favored over its plasma counterpart when evaluating a CNS tumor, either primary or metastatic, as it shows a higher concentration of ctDNA and a higher mutation detection rate, and it depicts the CNS lesion molecular profile more accurately, especially when dealing with brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis and follow-up of metastatic CNS lesions are typically performed with neuroimaging and CSF cytology; however, the latter suffer from low sensitivity [ 93 , 94 ]. NGS was found to outweigh the diagnostic performance of imaging and cytology in terms of sensitivity for the detection of brain metastases [ 62 , 95 98 ]. It was also able to detect targetable mutations in metastatic lung (e.g., EGFR , ALK , or ROS1 ) [ 62 , 96 , 97 , 99 102 ], melanoma [ 95 97 ], and breast cancer [ 96 ], also identify mechanisms of acquired resistance to therapy, such as the EGFR T790M mutation [ 96 , 103 106 ].…”
Section: Cns Cancersmentioning
confidence: 99%
“…Interestingly, new approaches have been introduced recently to improve the diagnostic accuracy of CSF. Circulating tumor DNA (ctDNA) might be promising but is not ubiquitously accessible [ 33 , 34 ]. Our patient collective also reflects the difficulty of accurately diagnosing LC.…”
Section: Discussionmentioning
confidence: 99%
“…However, up to 20% of patients with positive clinical and radiographic signs presented false-negative CSF cytology [ 72 , 73 ]. Several studies have shown that ctDNA can be detected in the CSF of patients with negative cytology analysis [ 20 , 27 , 32 , 74 ]. Cytology has limited sensitivity, and the analysis of ctDNA can complement the diagnosis of leptomeningeal metastases.…”
Section: Clinical Applications Of the Csf Ctdna For Cns Malignanciesmentioning
confidence: 99%